ANALISIS FAKTOR PENGARUH TERHADAP KEPERCAYAAN MANAJEMEN PENGGUNAAN BASIS DATA DALAM LAYANAN BISNIS UMKM DI INDONESIA: ANALYSIS OF INFLUENCE FACTORS ON MANAGEMENT TRUST IN USING DATABASES IN MSME BUSINESS SERVICES IN INDONESIA - Muhamad Dody Firmansyah; Henry Yono Zhang (LPPM Universitas Abdurrab, 2025)
Management's trust in the use of databases in business services plays an important role in supporting the growth of MSMEs (Micro, Small and Medium Enterprises) in Indonesia. The aim of this research is to analyze the factors that influence management's trust in the use of databases in MSME business services in Indonesia. Factors reviewed include data security, reliability, reputation, integrity and openness. The problem faced in this research is the difficulty of building trust in the use of databases, especially their impact in an increasingly competitive business world. This research uses mixed methods consisting of quantitative and qualitative methods to obtain more comprehensive results. The total quantitative data obtained from the questionnaire amounted to 290 respondents and the qualitative data obtained from interviews amounted to 40 respondents. The data collection technique was carried out using the cluster random purposive sampling method. Data analysis was carried out using SPSS software to analyze the data relationship between the variables studied. The research results show that quantitatively data security, reliability, reputation and openness have a significant influence in increasing management trust, while integrity does not have a significant influence. Qualitatively, data security and reputation influence user trust, while reliability, integrity and openness do not show a significant influence. This research can provide important understanding for MSMEs in Indonesia that improving data security and reputation can increase management trust in the use of databases in business services. It is hoped that this research can help MSMEs optimize the use of technology to improve their business services.